Students’ Perception on Avitourism Potential in Vegetated Area of Universitas Andalas - Ibrahim Fauzi; Rihadatul Aisyah; Negi Alfajri; Muhammad Nazri Janra (Universitas Atma Jaya Yogyakarta, 2026)
This study evaluated the potential of avitourism in the vegetated areas of Universitas Andalas, West Sumatra, through a two-day birdwatching simulation and campus community perception survey. The simulation was conducted on 7–8 December 2024 at three sites (Medicinal Garden, Biodiversity Park, and Biology Education and Research Forest) using casual birdwatching techniques combined with digiscoping to document sighted birds. In total, 26 species representing 25 genera, 19 families, and 7 orders were documented. These included five Near Threatened species, one species listed in CITES Appendix II, four nationally protected species, one Indonesian endemic Prinia familiaris, and two migrants. Passeriformes dominated the records, highlighting their ecological diversity and attractiveness for tourism. An online survey on 44 student respondents showed that 91% of them had at least basic understanding on ecotourism, 95% supported the inclusion of birds as ecotourism attractions, and 50% expressed willingness to pay for avitourism services. Bird aesthetics assessment identified Hemiprocne longipennis (84% score 5) and Eurylaimus ochromalus (80% score 5) as the most attractive species for birdwatching, where the most influencing factors for bird aesthetic were feather coloration, vocalization, behavior, and morphology. These results demonstrate that the vegetated area in Universitas Andalas has potential for avitourism initiatives. Campus-based avitourism can be integrated with biodiversity conservation, empowering environmental education, and generating sustainable tourism opportunities, while engaging communities in conservation-oriented activities that benefit both people and nature.